Functional Frequency Discrimination From Cortical Somatosensory Stimulation in Humans - Kramer, Daniel R.; Lamorie-Foote, Krista; Barbaro, Michael; Lee, Morgan; Peng, Terrance; Gogia, Angad; Liu, Charles Y.; Kellis, Spencer S.; Lee, Brian (Frontiers in Neuroscience, 2019)
Recently, efforts to produce artificial sensation through cortical stimulation of primary somatosensory cortex (S1) in humans have proven safe and reliable. Changes in stimulation parameters like frequency and amplitude have been shown to elicit different percepts, but without clearly defined psychometric profiles. This study investigates the functionally useful limits of frequency changes on the percepts felt by three epilepsy patients with subdural electrocorticography (ECoG) grids. Subjects performing a hidden target task were stimulated with parameters of constant amplitude, pulse width, and pulse duration, and a randomly selected set of two frequencies (20, 30, 40, 50, 60, 100 Hz). They were asked to decide which target had the “higher” frequency. Objectively, an increase in frequency was associated with an increase in perceived intensity. Reliable detection of stimulation occurred at and above 40 Hz with a lower limit of detection around 20Hz and a just-noticeable difference estimated at less than 10 Hz. These findings suggest that frequency can be used as a reliable, adjustable parameter and may be useful in establishing settings and thresholds of functionality in future BCI systems.